Governance in the Post‐War City: Historical Reflections on Public–Private Partnerships in the UK. (11th February 2012) - Shapely, Peter
<x xml:space="preserve">Abstract</x> Abstract Partnerships between the public and private sectors have been a central feature in the development of British cities since the nineteenth century. Many major civic projects, transport links and even industrial estates have been successfully completed thanks to government, central and local, working with private interests, developers and investors. After the second world war, however, these partnerships became fundamental to the redevelopment of urban Britain. While the state provided legislation, finance and policy directives, local government worked with the private sector to build social housing, new roads and schools. However, the council also relied on private investment to transform tired city centres by building new shopping centres, hotels and office blocks. While contemporary studies recognize the importance of these partnerships in the growth of cities since the 1980s, this article will look at their significance in a broader historical perspective, highlighting the pivotal role they played from the 1950s to the 1970s, and assessing their relevance not simply in terms of the material redevelopment of the built environment but also in what is revealed about urban governance. Résumé Les partenariats public‐privé ont marqué l'évolution des villes britanniques depuis le dix‐neuvième siècle. Beaucoup de grands projets municipaux, de liaisons de transport et même de zones industrielles ont été réalisés avec succès grâce à un gouvernement, central ou local, travaillant avec des acteurs privés, promoteurs et investisseurs. Après la Seconde Guerre mondiale, ces partenariats sont devenus essentiels à la rénovation de la Grande‐Bretagne urbaine. Tandis que l'État apportait le cadre législatif, le financement et les directives politiques, les autorités territoriales coopéraient avec le secteur privé pour construire logements sociaux, nouvelles routes et écoles. Cependant, le pouvoir local s'est aussi appuyé sur l'investissement privé pour transformer des centres‐villes défraîchis en centres commerciaux, hôtels et quartiers d'affaires nouveaux. Les études contemporaines reconnaissent l'importance de ces partenariats pour la croissance des villes depuis les années 1980, mais cet article s'attachera à leur place dans une perspective historique plus large, soulignant le rôle décisif qu'ils ont joués entre les années 1950 et 1970, et appréciant leur pertinence non seulement en termes de réaménagement physique de l'environnement construit, mais aussi par ce qu'ils révèlent sur la gouvernance urbaine.